MECHANISMS FOR THE REACTIONS OF THE ANOMERIC TETRA-O-ACETYL-D-GLUCOPYRANOSYL BROMIDES WITH PYRIDINE AND 2-PYRIDONE - R. U. Lemieux; A. R. MORGAN (1965)
Reaction of tetra-O-acetyl-α-D-glucopyranosyl bromide (I) with pyridine at high dilution gives a high yield of N-(tetra-O-acetyl-β-D-glucopyranosyl)-pyridinium bromide (II). The addition of tetra-n-butylammonium bromide diverts the reaction to the formation of the highly strained α-anomer (III) of II. It is contended that III arises from the β-anomer (IV) of I by way of a rearrangement of an intermediate formed between pyridine and the 1,2-acetoxonium ion (VIII) which readily arises by dissociation of IV. The formation of 2-pyridyl tetra-O-acetyl-α-D-glucopyranoside in >60% yield in the reactions of I with either 2-ethoxypyridine or 2-pyridone in the presence of tetra-n-butylammonium bromide is taken as supporting evidence for this novel type of rearrangement.